A review of leading COVID-19 vaccines, the quest for immune protection, and its key challenges. Part 4: Global Covid-19 vaccination campaign – supply and distribution logistical requirements and challenges. - Hartshorne, Johan; De Villiers, Pierre (My University, 2021)
Rationale • Rapid manufacturing and effective distribution of sufficient quantities of vaccines is paramount to launch a successful vaccination campaign that will successfully achieve herd immunity to interrupt the pandemic crisis. • The fundamental objective driving COVID-19 vaccine deployment is to ensure that all people have fair access to safe and effective COVID-19 vaccines. • The purpose of Part 4 of this series is to highlight the logistical and ethical challenges of the supply and distribution chain of COVID-19 vaccines. Key points • All phases of the COVID-19 vaccination campaign merits strong consideration from an ethical and logistical perspective. • Vaccines must be authorised by regulatory authorities before use. • Governmental implementation bottlenecks are the cause of the inability to vaccinate at-risk populations rapidly. • Productivity and manufacturing of mRNA-based vaccines remain low, and ultra-cold chain requirements impose significant storage and distribution challenges. • Viral vector-based vaccines are based on proven technology and expected to yield significantly higher annual volumes. • Recombinant protein subunit vaccines can be easily scaled up, are reasonably stable and easier to manage, but development is currently running months behind schedule. • Live attenuated and whole inactivated virus vaccines require regulatory-approved biosafety level 3 (BSL-3) facilities for development and manufacturing, thus have more safety hurdles, are more complicated and slower to develop, and therefore unpredictable to manufacture. • An effective vaccination campaign requires adequate procurement of vaccines and political will. • Health care workers and elderly adults are the highest priorities for vaccination. • Exposing vaccine distribution and implementation plans to scrutiny is critical. • Allocation of limited vaccines should be prioritised and based on the ethical principles of maximising benefits, minimising harms, fair and equal access, transparency, informed consent and trust. • Public trust can only be ensured through transparent communications and consistently applied allocation of safe, effective, and fair vaccines to everyone. • Safety and public trust are critical considerations in vaccine acceptance. • Health care professionals are the most trusted source of information. Public health implications • Access to vaccines for global distribution before the end of 2021 will be a task of unprecedented proportions. • Experts recommend that governments invest in a more expansive and diversified portfolio of vaccines. • Many countries are under-resourced with vulnerable high-risk communities. • Multiple stakeholders are driving a global approach to equitable access. • Public distrust, anti-vaccine messaging, and vaccine hesitancy are a significant concern to vaccine campaign efficacy to contain the pandemic.
Keywords: acceptance; accessibility; allocation; availability; COVID-19 vaccines; distribution; equitable distribution; ethicals; logistics; manufacturing; procurement; storage; supply chain; tracking; vaccination campaign; vaccine hesitation; verification